The Use of the Short-Cut Graphic Method of Multiple Correlation: Concluding Remarks - Malenbaum, Wilfred (Quarterly Journal of Economics, 1940)
Concluding Remarks Get access Wilfred Malenbaum Wilfred Malenbaum Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 2, February 1940, Pages 358–364, https://doi.org/10.2307/1883343 Published: 01 February 1940